Bronze Age Fashion in Syria - Archi, Alfonso (Biblical archaeology review, 2021)
The article discusses Bronze Age fashion in Syria. It discusses statuette from Ebla wears that either a queen or a goddess wear a gold dress and a wig and the dress consists of a heavy mantle with decorative rows of woolen tufts and openings in the front for the arms. It also mentions that wooden carving shows King Irkab-damu of Ebla dressed in a turban and a cloak and decorated with five rows of woolen tufts.